IRELAND ON SCREEN. A VIEW FROM SPAIN - González Casademont, Rosa (International Journal of English Studies, 2002)
The essay considers the vast output of existing cinematic representations of Ireland, prior to discussing one of its main strands -the persistent representation of Ireland as a pastoral Arcadia- and its most exemplary piece: John Ford's film The Quiet Man (1952). It is argued that despite being credited with fostering an amusing and condescending visual image of stage Irishness Ford gives plenty of clues for viewing his portrayal critically. These have been missed by audiences world-wide but are picked up and elaborated on four decades later by Spanish film director José Guerín in his film Innisfiee (1990).